2019
DOI: 10.1101/19009407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Violin plot data: A concerto of crucial information on valve thrombogenicity categorized in vitro by valve motion and inferred flow velocity

Abstract: Objectives: We hypothesize that prosthetic valve thrombogenic potential may be inferred by valve regional flow velocity. This metric was used to compare two clinical valves and two experimental prototypes. Methods: Four our clinical and experimental prototype valve models were tested in aortic and mitral sites under pulsatile circulation in a pulse duplicator. An optical approach measuring projected dynamic valve area to gauge valve motion was implemented. Pulsatile pressures and flow rates were measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 31 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Readers will note that in prior publications, closing flow velocities in excess of those observed in this study were reported [5][6][7][8][9][10]. Previous records with excessive closing flow velocities have been rectified in this report by re-analysis of the historical experiment test datasets imported into revised EXCEL templates.…”
Section: Edited Vs Unedited Instantaneous Flow Ratesmentioning
confidence: 95%
See 4 more Smart Citations
“…Readers will note that in prior publications, closing flow velocities in excess of those observed in this study were reported [5][6][7][8][9][10]. Previous records with excessive closing flow velocities have been rectified in this report by re-analysis of the historical experiment test datasets imported into revised EXCEL templates.…”
Section: Edited Vs Unedited Instantaneous Flow Ratesmentioning
confidence: 95%
“…Over time, progressive adaptations to the pulse duplicator apparatus have been reported [1][2][3][4][5][6][7][8][9][10][11][12]. This included the optical measurement of valve kinematics and in silico evaluations [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Pulse Duplicator Experiments and Computational Modelingmentioning
confidence: 99%
See 3 more Smart Citations